Mozambique's social protection system: An overview of the Basic Social Subsidy Programme (PSSB), the Direct Social Action Programme (PASD), the Productive Social Action Programme (PASP) and the Social Assistance Services (PAUS) - Pedro Lara de Arruda (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Mozambique is a low-income, Southern African nation with an estimated population of 28 million people, 67 per cent of whom live in rural areas. Women comprise 51 per cent of the population, and 45 per cent of the population are under 15 years old (World Bank 2015). [...]
Keywords: 330; Mozambique; social protection; system; overview; Basic Social Subsidy Programme; PSSB; Direct Social Action Programme; PASD; Productive Social Action Programme; PASP; Social Assistance Services; PAUS